The old woman, the tulip, and the dog - Ostriker, Alicia (Pitt poetry series., 2014)
This book by a major American poet is for poetry readers at all levels, academic and non-academic. It is a sequence of poems that will surprise and delight readers-in the voices of an old woman full of memories, a glamorous tulip, and an earthy dog who always has the last word.